DEVELOPMENT OF AFFECTIVE ASSESSMENTS ON STUDENT ENGAGEMENT IN LEARNING INDONESIAN LANGUAGE - Pani, Pani; Handayani , Dina Fitria (PT. Antis International Publisher, 2024)
The aim of this research is to develop an affective assessment to measure student participation in learning Indonesian. Effective assessment must include emotional dimensions, attitudes and values ​​that support student participation in the learning process. Assessment tools that integrate the principles of polite language skills not only measure student participation and interest, but also ensure that classroom interactions reflect the values ​​of politeness and respect. The method used in this research includes a literature review. The research results show that the developed affect assessment can provide a comprehensive picture of students' affective engagement and positively improve the quality of Indonesian language learning. Active and responsible student participation is expected to support the achievement of comprehensive and meaningful educational goals.